Thuiaria longstaffi Hickson & Gravely 1907 ... - Soto, Joan J.; Peña, Álvaro L. (Zenodo, 2019)
Tubularia longstaffi Hickson & Gravely, 1907 (Fig. 4 a–i) Material examined. ANT XVII/3: 111-5, few stems, up to 45 mm high, on O. terranovae; 111-7, some stems, up to 40 mm high, with developing gonophores; 111-9, some stems, up to 110 mm, with mature gonophores. Remarks. The specimens examined here concurs with all the diagnostic features mentioned in the redescription of the type material of T. longstaffi by Peña Cantero (2017): yellow stems, in entwined clusters, tube diameter increasing distally (Fig. 4a), with transversal ridges; polyps large, up to 5 x 5 mm, with an oral crown of 29–37 tentacles and an aboral one of 12–19 tentacles; type and size of nematocysts, and gonophores as cryptomedusoids (Fig. 4d, g–h). Additional knowledge regarding sexual dimorphism and early developmental stages is drawn from the present study. Male blastostyles elongate, c. 4 mm long and with up to 17 stalked gonophores as cryptomedusoids (Fig. 4c). Gonophore maturity increasing distally: recently formed gonophores ... : Published as part of Soto, Joan J. & Peña, Álvaro L., 2019, Benthic hydroids (Cnidaria, Hydrozoa) from the Weddell Sea (Antarctica), pp. 1-78 in Zootaxa 4570 (1) on page 15, DOI: 10.11646/zootaxa.4570.1.1, http://zenodo.org/record/2608527 ...